Attention bias and anxiety in young children exposed to family violence. (2nd March 2015) - Briggs‐Gowan, Margaret J.; Pollak, Seth D.; Grasso, Damion; Voss, Joel; Mian, Nicholas D.; Zobel, Elvira; McCarthy, Kimberly J.; Wakschlag, Lauren S.; Pine, Daniel S.
<x xml:space="preserve">Abstract</x> Background Attention bias toward threat is associated with anxiety in older youth and adults and has been linked with violence exposure. Attention bias may moderate the relationship between violence exposure and anxiety in young children. Capitalizing on measurement advances, this study examines these relationships at a younger age than previously possible. Methods Young children (mean age 4.7, ±0.8) from a cross‐sectional sample oversampled for violence exposure (N = 218) completed the dot‐probe task to assess their attention biases. Observed fear/anxiety was characterized with a novel observational paradigm, the Anxiety Dimensional Observation Scale. Mother‐reported symptoms were assessed with the Preschool Age Psychiatric Assessment and Trauma Symptom Checklist for Young Children. Violence exposure was characterized with dimensional scores reflecting probability of membership in two classes derived via latent class analysis from the Conflict Tactics Scales: Abuse and Harsh Parenting. Results Family violence predicted greater child anxiety and trauma symptoms. Attention bias moderated the relationship between violence and anxiety. Conclusions Attention bias toward threat may strengthen the effects of family violence on the development of anxiety, with potentially cascading effects across childhood. Such associations may be most readily detected when using observational measures of childhood anxiety.